Level of sedation in critically ill adult patients: a protocol for a systematic review with meta-analysis and trial sequential analysis - Candice Delcourt; Niklas Nielsen; Anders Aneman; Markus B Skrifvars; Anthony Delaney; Michael C Reade; Johanna Hästbacka; Johan Holgersson; Ameldina Ceric; Teresa May; Manoj Saxena; Janus Jakobsen (BMJ Open, 2022)
Introduction It is standard of care to provide sedation to critically ill patients to reduce anxiety, discomfort and promote tolerance of mechanical ventilation. Given that sedatives can have differing effects based on a variety of patient and pharmacological characteristics, treatment approaches are largely based on targeting the level of sedation. The benefits of differing levels of sedation must be balanced against potential adverse effects including haemodynamic instability, causing delirium, delaying awakening and prolonging the time of mechanical ventilation and intensive care stay. This systematic review with meta-analysis aims to investigate the current evidence and compare the effects of differing sedation levels in adult critically ill patients.Methods and analyses We will conduct a systematic review based on searches of preidentified major medical databases (eg, MEDLINE, EMBASE, CENTRAL) and clinical trial registries from their inception onwards to identify trials meeting inclusion criteria. We will include randomised clinical trials comparing any degree of sedation with no sedation and lighter sedation with deeper sedation for critically ill patients admitted to the intensive care unit. We will include aggregate data meta-analyses and trial sequential analyses. Risk of bias will be assessed with domains based on the Cochrane risk of bias tool. An eight-step procedure will be used to assess if the thresholds for clinical significance are crossed, and the certainty of the evidence will be assessed using Grades of Recommendations, Assessment, Development and Evaluation.Ethics and dissemination No formal approval or review of ethics is required as individual patient data will not be included. This systematic review has the potential to highlight (1) whether one should believe sedation to be beneficial, harmful or neither in critically ill adults; (2) the existing knowledge gaps and (3) whether the recommendations from guidelines and daily clinical practice are supported by current evidence. These results will be disseminated through publication in a peer-reviewed journal.